12th IET International Conference on AC and DC Power Transmission (ACDC 2016) 2016
DOI: 10.1049/cp.2016.0426
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fault Current Limiter on VSC-HVDC DC Protection

Abstract: Multi-terminal Voltage-Sourced Converter (VSC) High Voltage Direct Current (HVDC) transmission is expected to play a key role in future power transmission grids. Compared with AC transmission, DC transmission is more vulnerable to faults due to the lower DC side impedances and sensitive power electronics used in the converters. DC protection issues must be solved before any multi-terminal VSC-HVDC grid can be established. In terms of DC protection, apart from using a DC circuit breaker to interrupt and isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…However, SFCL parameter optimization, economic performance analysis, design of electrical insulation are not yet investigated. Superconducting fault current limiters have been studied in VSC-HVDC systems [31][32][33][34][35][36][37]. A novel SFCL with both a superconducting coil and a resistance is presented for limiting rapidly growing current in VSC-HVDC systems during severe disturbances [32].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, SFCL parameter optimization, economic performance analysis, design of electrical insulation are not yet investigated. Superconducting fault current limiters have been studied in VSC-HVDC systems [31][32][33][34][35][36][37]. A novel SFCL with both a superconducting coil and a resistance is presented for limiting rapidly growing current in VSC-HVDC systems during severe disturbances [32].…”
mentioning
confidence: 99%
“…A novel SFCL with both a superconducting coil and a resistance is presented for limiting rapidly growing current in VSC-HVDC systems during severe disturbances [32]. A DC protection scheme of multiterminal VSC-HVDC with resistive type SFCL was presented [34]. Resistive type SFCLs reduce the current rating of DC circuit breakers.…”
mentioning
confidence: 99%
“…In this case, a proactive hybrid DC CB with a superconducting fault current limiter in the main branch is proposed in [171] and the feasibility analysis of this configuration is performed in [172]. Also, the impact of superconducting fault current limiter on fault current interruption in MT-HVDC systems using continuous wavelet transform protection scheme and the proactive hybrid DC CB is investigated in [173]. It is shown that superconducting fault current limiter significantly reduces the DC fault current interruption requirements of hybrid DC CBs.…”
Section: Other Types Of DC Circuit Breakersmentioning
confidence: 99%
“…Refs. [26][27][28][29] proposed an appropriate protection strategy applicable to a MTDC using both SFCL and DCCB; however, previously mentioned studies mainly focus on the combination of a resistive-type SFCL and a DCCB. Botong Li, et al studied a SI-SFCL applicable to a HVDC system, and a recent study dealt with the design key parameter selection method to satisfy the interrupting performance of a commercial hybrid DCCB through an equivalent model [30,31].…”
Section: Introductionmentioning
confidence: 99%